THE CHARACTERISTICS OF INNOVATOR SCHOOL PRINCIPAL AS A LEADER THE CASE FROM ROMANIA - Mariana Dogaru; Ioan Neacsu (European Scientific Journal, ESJ, 2014)
The school principal is the most influential person within a school.So, it is very important to find out the complete characteristics of effectiveschool principal from an effective school called ―successful school‖. It is forthe first time in Romania when a complete inventory of features of aneffective school principal was identified according the opinion of specialists(persons that are in charge with school improvement). Also, for the first timein Romania we identified the characteristics of effective school fromRomania, described by the specialists. The research was conducted during2012.